The Commons Tools for Reading, Writing, and Rhetoric - Parrot, Jill M; Ashby, Dominic J; Collins, Jonathon (Open textbook library., 2022)
An Open Textbook for English 101: Reading, Writing, and Rhetoric at Eastern Kentucky University